13C-glucose breath test quantifies differences in glucose metabolism between endurance and non-athletes - Takahiko J Fujimi; Yuko Mekata; Kaori Kikuchi; Kyoka Musha; Tomokazu Matsuura (Japanese Society of Physical Fitness and Sports Medicine, 2023)
Physical training changes the metabolic state, but such changes are difficult to quantify directly and non-invasively in humans. This study therefore used breath tests with 13C stable isotope glucose to assess glucose metabolism in endurance athletes. Our breath test measured the ratio of 13C to 12C in CO2 from expired air to derive 13C excretion per unit time. We compared 13C excretion levels between long-distance runners (runner group) and non-trained healthy males (control group), in both conditions with and without 50 g oral glucose loading (OGL). The 13C excretion was lower in the runner group than in the control group throughout the 6-hour period, regardless of OGL. Therefore, the area under the curve, which indicates total excretion, was lower in the runner group. There are many reports related to the adaptation of glucose metabolism in training (including gluconeogenesis, glucose transport to the liver and muscle, and glycogen synthesis). Our study showed that this breath test could be a simple and convenient way to monitor the overall glucose metabolic adaptation state in the athlete body.